Teaching study skills : a guide for teachers - Devine, Thomas G., 1928- 4 0 16; 5 (Boston : Allyn and Bacon, 1981)
A handbook of proven strategies and techniques to improve study skills in every subject area--from spelling to math--Cover.
Includes bibliographies and index.
Keywords: 2 -- 0; 6; Study skills;Study skills -- Handbooks, manuals, etc.;Handbooks, manuals, etc; 20; 2